Mechanism of EHMT2-mediated genomic imprinting associated with Prader-Willi syndrome - Sung Eun Wang; Yubao Cheng; Jaechul Lim; Mi-Ae Jang; Emily N. Forrest; Yuna Kim; Meaghan Donahue; Sungsin Jo; Sheng-Nan Qiao; Dong Eun Lee; Jun Young Hong; Yan Xiong; et al. (Nature Communications)
Abstract Prader-Willi Syndrome (PWS) is caused by the loss of expression of paternally expressed genes in the human 15q11.2-q13 imprinting domain. A set of imprinted genes that are active on the paternal but silenced on the maternal chromosome are intricately regulated by a bipartite imprinting center (PWS-IC) located in the PWS imprinting domain. We previously discovered that euchromatic histone lysine N-methyltransferase-2 (EHMT2/G9a) inhibitors are capable of un-silencing PWS-associated genes by restoring their expression from the maternal chromosome. Here, in mice lacking the Ehmt2 gene, we document un-silencing of the imprinted Snrpn/Snhg14 gene on the maternal chromosome in the late embryonic and postnatal brain. Using PWS and Angelman syndrome patient derived cells with either paternal or maternal deletion of 15q11.2-q13, we have found that chromatin of maternal PWS-IC is closed and has compact 3D folding confirmation. We further show that a distinct noncoding RNA (TSS4-280118) preferentially transcribed from the upstream of the PWS-IC of maternal chromosome interacts with EHMT2 and forms a heterochromatin complex in CIS on the maternal chromosome. Inactivation of TSS4-280118 by CRISPR/Cas9 editing results in unsilencing of the expression of SNRPN and SNORD116 from the maternal chromosome. Taken together, these findings demonstrate that allele-specific recruitment of EHMT2 is required to maintain the maternal imprints. Our findings provide mechanistic insights and support a model for imprinting maintenance of the PWS imprinted domain.